(untitled) (International relations and international law Journal, 2016)
With emergence of the concept of Sustainable Development ecological priorities become an indispensable component of any national strategy of development, the basis for definition of the purposes and the directions of both internal and foreign policy. The concept of Sustainable Development appeared as a result of integration of three main points: economic, social and ecological. In compliance with it there is often raise discussion of three purposes of sustainable development: ecological integrity, eco-effectiveness and eco-justice. This article is devoted to the European countries experience studying as they first approved sustainable development at the state level like a main direction of domestic and international policy. The article is dealing with the processes of formation and realizations of national strategies of sustainable development of a number of the European countries and the European strategy of sustainable development in the complex analysis.